An Euler–Lagrange particle approach for modeling fragments accelerated by explosive detonation. (1st December 2015) - Price, Matthew A.; Nguyen, Vinh‐Tan; Hassan, Oubay; Morgan, Ken
Summary: In this paper, a method is proposed for modeling explosive‐driven fragments as spherical particles with a point‐particle approach. Lagrangian particles are coupled with a multimaterial Eulerian solver that uses a three‐dimensional finite volume framework on unstructured grids. The Euler–Lagrange method provides a straightforward and inexpensive alternative to directly resolving particle surfaces or coupling with structural dynamics solvers. The importance of the drag and inviscid unsteady particle forces is shown through investigations of particles accelerated in shock tube experiments and in condensed phase explosive detonation. Numerical experiments are conducted to study the acceleration of isolated explosive‐driven particles at various locations relative to the explosive surface. The point‐particle method predicts fragment terminal velocities that are in good agreement with simulations where particles are fully resolved, while using a computational cell size that is eight times larger. It is determined that inviscid unsteady forces are dominating for particles sitting on, or embedded in, the explosive charge. The effect of explosive confinement, provided by multiple particles, is investigated through a numerical study with a cylindrical C4 charge. Decreasing particle spacing, until particles are touching, causes a 30–50% increase in particle terminal velocity and similar increase in gas impulse. Copyright © 2015 John Wiley & Sons, Ltd.